UPAYA PENCEGAHAN RISIKO PASIEN JATUH DI RAWAT INAP - Zarah, Maharani; Djunawan, Achmad (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Patient safety is one of the important things that need to be considered in nursing care in hospitals. Patient safety consists of 6 goals from the six patient safety goals, the incidence of falls is still a worrying thing for all inpatients in hospitals. Prevention efforts can be carried out by obediently carrying out an assessment and preventing the risk of falling in accordance with the high score of the patient's low risk. This literature review study aims to find out how to prevent the risk of falling patients in inpatient care. The method used is a literature review approach with survey paper techniques, searching for journal databases and relevant library sources. This literature review study was obtained from searching research articles from 2011–2020 using Goggle Scholar, Garuda and One Search. There are 10 journals that match the inclusion criteria and according to the research question. The population is inpatient nurses in hospitals. The results based on 10 research journals showed that 9 hospitals with the majority of nurses were obedient in carrying out a patient fall risk assessment and 1 hospital the majority of nurses were not obedient. And efforts to prevent the risk of falling patients have been carried out in hospitals